Enhanced Efficacy and Reduced Hepatotoxicity by Combination of Gnaphalium affine Extract and Benzbromarone in the Treatment of Rats with Hyperuricemic Nephropathy - Liu, Fei; Liu, Xi-Zi; Yang, Qian; Han, Shi-Yi; Fan, Si-Yang (Pharmaceutical Fronts, 2021)
Simultaneous oral intake of herbal medicine with chemical drugs may result in beneficial pharmacodynamic efficacy, including additive and synergistic effects with reduced toxicity. Gnaphalium affine D. Don (GAD) is a traditional Chinese Medicine that has been used for the management of hyperuricemia and gout. Benzbromarone (BBR) is one of the first-line drugs used for urate-lowering therapy in China but is toxic to the liver. The present study aimed to determine the effects of GAD and BBR, both alone and in co-treatment (with dosing interval of 1 hour), on chronic hyperuricemic nephropathy (HN) and hepatotoxicity in rats. Our data indicated that GAD significantly inhibited the elevation of serum uric acid, blood urea nitrogen, and creatinine levels in chronic HN rats at doses of 450 and 900 mg/kg/day. The rise in serum alanine aminotransferase and aspartate aminotransferase in BBR (or vehicle)-treated HN rats was significantly reduced by pre- (or post)-administration of GAD (450 mg/kg/day). The q-value >1.15 (by Jin method) indicated synergistic effects of co-treatments of BBR (50 mg/kg) with GAD (450 mg/kg). The synergistic beneficial effects were validated by comparison of BBR alone at a dose of clinical usage (4.5 mg/kg/day, in two divided doses) and BBR + GAD at half dose plus half dose (2.25 + 225 mg/kg/day) or half dose plus full dose (2.25 + 450 mg/kg/day). In conclusion, co-treatment with GAD and BBR holds promise for the management of hyperuricemia and gout.
Keywords: Gnaphalium affine D. Don; benzbromarone; co-treatment; hyperuricemia; hepatoprotection